Effects of IMOD(™) on angiogenesis, miR-503 and CDC25 expression levels in heart tissue of diabetic male rats - Ghaffari-Nasab, Arshad (Avicenna J Phytomed, 2018)
OBJECTIVE: Diabetes is associated with vascular complications and impaired angiogenesis. Since angiogenesis plays a crucial role in vascular homeostasis in ischemic heart diseases, in this study, the effect of IMOD™ on miR-503 and CDC25 expression level which are altered in impaired angiogenesis were investigated in heart tissue of diabetic rats. MATERIALS AND METHODS: Forty male Wistar rats (200-250 g) were randomly classified into 4 groups: control (C), IMOD™ (I), diabetes (D), and diabetes+IMOD™ (D+I). For induction of experimental diabetes in animals, a single dose of streptozotocin (STZ; 60mg/kg) was injected intraperitoneally. After 8 weeks of treatment with IMOD™ (20 mg/kg/day), heart tissue samples were removed and used for measurement of miR-503 and CDC25 expression level as well as histological studies. RESULTS: Results of this study showed that diabetes decreased heart tissue angiogenesis which was associated with increased miR-503 and reduced CDC25 expression levels (p<0.05) and IMOD™ could reduce the expression of miR-503 and increase the expression of CDC25 (p<0.05). Moreover, IMOD™ extensively induced angiogenesis in the heart tissue of diabetic group. However, IMOD™ had no significant effect on expressions of miR-503 and CDC25, or angiogenesis in healthy rats. CONCLUSION: This study showed that IMOD™ is able to increase angiogenesis in the heart tissue of diabetic rats. The angiogenic effect of IMOD™ is associated with reduction of miR-503 expression and increased expression of CDC25.